Basic physics of nuclear medicine - Maher, Kieran (Wikibooks, 2013)
Nuclear Medicine is a fascinating application of nuclear physics. The first ten chapters of this wikibook are intended to support a basic introductory course in an early semester of an undergraduate program. They assume that students have completed decent high school programs in maths and physics and are concurrently taking subjects in the medical sciences. Additional chapters cover more advanced topics in this field. Our focus in this wikibook is the diagnostic application of Nuclear Medicine.